The Characteristics of Postpartum Mothers to the Success of Breastfeeding in the First 3 Months - Indah Yun Diniaty Rosidi; Mardiana Ahmad; Veni Hadju (STIKes Patria Husada Blitar, 2020)
Exclusive breastfeeding plays a major role in reducing the infant mortality rate while the achievement of exclusive breastfeeding in Indonesia is still very low due to various factors. This research aimed to determine the effect of the characteristics of puerperal women to the success of exclusive breastfeeding in the first 3 months. The research design was an analytical survey of an explanatory research approach. The sample of the research was postpartum mothers who had babies aged 3 as many as 90 people who were willing to become respondents. The sample was observed by using a checklist of breastfeeding techniques and breastfeeding success. The data were analyzed using the Chi-Square test and the Mann Withney test. The results of the research showed that there was no significant correlation between age (Ï = 0.075), education (Ï = 0.145), occupation (Ï = 0.136), gravida (Ï = 0.530), maternal residence status (Ï = 0.134) and the success of breastfeeding ( Ï> 0.05). So it could be concluded that there was no correlation between maternal characteristics to the breastfeeding success. I is needed to give intensive education to increase the mother's knowledge about exclusive breastfeeding.